Delivery Performance Improvement Using Six Sigma Method: A Case Study At Fmc Agricultural Manufacturing - Satyana Primandaru; Soeparno Soeparno (Institut Teknologi Sepuluh Nopember, 2019)
PT. FMC is a manufacturing company in producing pesticides and classified into 3 herbicides, fungicides and insecticides. The use of pesticides is very important to maintain the quality of the crop, the delivery of products may not be late because it will disrupt the consumer production chain but unfortunately PT. FMC delivery performance has a big issue, delivery is an important metric because influences to customer satisfaction. This research focuses on how companies are able to identify problems, analyze and solve these problems using the Six Sigma methodology. The method is used because the method has a cycle of how companies solve a problem that can disrupt business processes. And the results of research in finding problems in this business process are (1) problems triggered by delays in the arrival of material both raw material and packaging material. (2) the customer delays delivery several times (3) the Warehouse Leader is late in inputting data and Post Goods Issue.